Artificial Intelligence Efficiency In Promoting The Digitalization Of Keris Msmes In Sumenep - Ahmad Ghufrony; Syamsul Arifin; Fathorrohman (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
Digital transformation has become a strategic necessity for Micro, Small, and Medium Enterprises (MSMEs) to enhance operational efficiency, competitiveness, and business sustainability in the digital economy era. One technology with considerable potential to support this process is Artificial Intelligence (AI). This study aims to examine the efficiency of AI utilization in accelerating the digitalization of keris craft MSMEs in Sumenep Regency, while also identifying the role of AI in business learning, decision making, and the enhancement of creativity rooted in local wisdom. The research adopts a qualitative approach, with data collected through in depth interviews involving eight informants, including MSME practitioners, community members, village government officials, and representatives of the MSME Office. The findings indicate that AI demonstrates substantial relevance and efficiency in supporting the digital transformation of keris MSMEs in Sumenep by improving operational efficiency, optimizing digital marketing strategies, strengthening supply chain management, and enhancing customer service quality. Furthermore, AI’s learning and reasoning capabilities play a critical role in enabling MSMEs to conduct data-driven market analysis, production planning, risk management, and more rational strategic decision-making. From a creative perspective, AI functions as an innovative partner that facilitates product design development, keris personalization, and the strengthening of brand narratives, while preserving the integrity of local cultural identity. This study concludes that the integration of AI encompassing learning, reasoning, and creativity constitutes a strategic factor in reinforcing the digitalization and competitiveness of keris MSMEs in Sumenep, while simultaneously supporting business sustainability and the preservation of local cultural heritage within the framework of the digital economy.